Bioconversion and bioaccessibility of isoflavones from sogurt during in vitro digestion. (1st May 2021) - Ningtyas, Dian Widya; Hati, Subrota; Prakash, Sangeeta
Highlights: Yoghurt culture with modest viable counts survived simulated gastric digestion. Maximum aglycones produced from sogurt in enteric phase II with 8U β-glucosidase. Confocal microscopy capable of capturing maximum protein digestion in gastric phase. Abstract: This study investigated the bioconversion and bioaccessibility of soy isoflavones produced in sogurt fermented with S. thermophilus and L. bulgaricus during in vitro digestion . The highest survivability of S. thermophilus (6.49 log cfu/mL) and L. bulgaricus (6.48 log cfu/mL) was in oral phase. In gastric phase, the total aglycones of sogurt (26.73 g/L) increased up to 20 times than control (1.21 g/L), with a significant increase in daidzein (17.05 g/L) and genistein (9.68 g/L). Addition of 8U of β-glucosidase into soymilk significantly increased the conversion of isoflavone in ENTII (daidzein: 0.46 g/L; genistein: 0.18 g/L) than in ENTI (daidzein: 0.33 g/L; genistein: 0.20 g/L). The particle size analysis and confocal micrographs of digesta also suggest the size of fat and protein in gastric phase to be smaller than in intestinal phase. The results indicate the prospective to develop soy-based fermented products capable of releasing high isoflavone in the digestive system.